A Ajaran Upanisad Dalam Menanamkan Sikap Cinta Kasih Bagi Umat Beragama Hindu - Kadek Ayu Putri Oktaviani (Jurnal Pendidikan Agama, 2022)
This paper aims to provide knowledge to the community, especially the Hindu community regarding the teachings contained in the Upanishads, because in this era of globalization people tend to be more concerned with material so they forget to study religious teachings, even though in this day and age understanding of religious teachings is necessary to counteract bad things caused by the rapid advancement of technology. Instilling an attitude of love is very much needed nowadays because the phenomenon in the community often occurs in bad deeds such as rounding up, torture committed, on fellow humans and animals. In the Upanisad there are many teachings such as the teachings of Ethics, the Nature of Atman and Brahman as well as the teachings of Moksa which are very important to be used as guidelines for the Hindu religious community in daily life. Keywords: Upanishads, Love, Hinduism.